Pemilihan Pemasok Bahan Mentah pada Restoran Menggunakan Metode Fuzzy Analytical Hierarchy Process - Elta Sonalitha; M. Sarosa; Agus Naba (Jurnal EECCIS, 2015)
Production in the restaurant is a continuous production that must be provided with uncertain request based on the consumer demand. Availability of raw materials is preferred to support the production process. In purchasing management it is often difficult to choose the right supplier of raw materials for each process order. The purpose of this research is to implement the method of Fuzzy Analytical Hierarchy Process (FAHP) in the Decision Support System (DSS) purchase of raw materials to suppliers. The addition of fuzzy logic in AHP is used to enhance the accuracy of subjectivity in the process of purchasing management assessment for each criteria and alternatives.The analysis includes a comparison with the results of manual calculations based SPK FAHP and accuracy of the final system with expert recommendations for the management of the purchase order process of DSS.The results showed an increase in profit of the accuracy of the selection of suppliers restaurant using FAHP method compared with the manual method. The analysis shows a significant difference when applied to the same material, fixed price of each supplier but different number of purchases, able to provide the difference in price which means lower costs and increase profits purchase.Index Terms — DSS, FAHP, Supplier Management, Order Management, Raw Material, FAHP.